Eradication of Acinetobacter baumannii/Enterobacter cloacae complex in an open proximal tibial fracture and closed drop foot correction with a multidisciplinary approach using the Taylor Spatial Frame®: a case report - G. Siebenbürger; B. Grabein; T. Schenck; C. Kammerlander; W. Böcker; C. Zeckey (European Journal of Medical Research, 2019)
Abstract Background Multi-drug-resistant bacteria (e.g. Carbapenem-resistant Acinetobacter baumannii, extended-spectrum betalactamase or carbapenemase-producing enterobacteriaceae) are emerging in early-onset infections. So far, there is no report describing the eradication of these bacteria in a osseous infection of an open proximal tibial fracture in combination with the hexapod technology to address both osseous consolidation and closed drop foot correction. Case presentation After sustaining a proximal tibial fracture (Gustilo 3B), a 41-year-old man was primarily treated with open reduction and internal fixation by a locking plate and split-thickness skin graft in the home country. At the time of admission to our hospital there was a significant anterolateral soft tissue defect covered with an already-necrotic split-thickness graft and suspicious secretion. CAT and MRI scans revealed no signs of osseous healing, intramedullary distinctive osteomyelitis, as well as a large abscess zone in the dorsal compartment. Multiple wound smears showed multi-drug-resistant bacteria: Acinetobacter baumannii (Carbapenem resistant) as well as Enterobacter cloacae complex (AmpC overexpression). After implant removal, excessive osseous and intramedullary debridements using the Reamer Irrigator Aspirator (RIA®) as well as initial negative pressure wound therapy were performed. Colistin hand-modelled chains and sticks were applied topically as well as an adjusted systemic antibiotic scheme was applied. After repetitive surgical interventions, the smears showed bacterial eradication and the patient underwent soft tissue reconstruction with a free vascularized latissimus dorsi muscle flap. External fixation was converted to a hexapod fixator (TSF®) to correct primary varus displacement, axial assignment and secure osseous healing. A second ring was mounted to address the fixed drop foot in a closed fashion without further intervention. At final follow-up, 12 months after trauma, the patient showed good functional recovery with osseous healing, intact soft tissue with satisfactory cosmetics and no signs of reinfection. Conclusions A multidisciplinary approach with orthopaedic surgeons for debridement, planning and establishing osseous and joint correction and consolidation, plastic surgeons for microvascular muscle flaps for soft tissue defect coverage as well as clinical microbiologists for the optimized anti-infective treatment is essential in these challenging rare cases. Level of evidence Level IV.